A Student Guide to Collaborative Writing with CECE Talk A Computer Network Tool - Neuwirth, Christine M.; Carnegie Mellon Univ., Pittsburgh, PA. Center for Educational Computing in English ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
Developed for use with collaborative writing activities in conjunction with the Center for Educational Computing in English (CECE) Talk Program, this student guide provides sample activities for collaborative writing as well as detailed examples of the activities. The examples begin with a short exchange between people using the talk program to participate in the exercise and go on to show how a writer would make use of the results by using the printout of the session provided by the talk program to help plan, generate ideas, and revise. Sections of the guide include: (1) brainstorming; (2) discussing your paper with a partner; (3) what do readers expect?; (4) role-playing with writing; (5) sample questions for role-playing; and (6) using a reader's questions, summaries, requests for clarifications and predictions to inform your writing. (RS)
ERIC Note: For the companion instructor's guide, see CS 211 877.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audience Response; Brainstorming; Collaborative Writing; Computer Assisted Instruction; Higher Education; Process Approach (Writing); Role Playing; Writing Exercises; Guides, Classroom -- Learner